2019
DOI: 10.5194/bg-16-713-2019
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance of a restored and cutover raised bog: implications for restoration and comparison to global trends

Abstract: Abstract. The net ecosystem exchange (NEE) and methane (CH4) flux were measured by chamber measurements for five distinct ecotypes (areas with unique eco-hydrological characteristics) at Abbeyleix Bog in the Irish midlands over a 2-year period. The ecotypes ranged from those with high-quality peat-forming vegetation to communities indicative of degraded, drained conditions. Three of these ecotypes were located in an area where peat was extracted by hand and then abandoned and left to revegetate naturally at le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 68 publications
(123 reference statements)
5
37
0
Order By: Relevance
“…Rewetted peatlands may experience a decrease in CO 2 fluxes and respiration rates after rising water level (Komulainen et al 1999;Tuittila et al 1999;Hendriks et al 2007;Waddington, Strack, and Greenwood 2010b;Urbanová, Picek, and Bárta 2011;Urbanová et al 2012;Strack and Zuback 2013;Cui et al 2017;Kareksela et al 2015;Knox et al 2015;Karki et al 2016;Wilson et al 2016;Lee et al 2017;Musarika et al 2017;Swenson et al 2019;Renou-Wilson et al 2019;Holl, Pfeiffer, and Kutzbach 2020;Rodriguez, Gerber, and Daroub 2020). For example, the CO 2 emission level decreased by 31% in agricultural fens after raising the water level by 20 cm (Matysek et al 2019).…”
Section: Effects Of Water Level Alteration On Co 2 Emissionsmentioning
confidence: 99%
“…Rewetted peatlands may experience a decrease in CO 2 fluxes and respiration rates after rising water level (Komulainen et al 1999;Tuittila et al 1999;Hendriks et al 2007;Waddington, Strack, and Greenwood 2010b;Urbanová, Picek, and Bárta 2011;Urbanová et al 2012;Strack and Zuback 2013;Cui et al 2017;Kareksela et al 2015;Knox et al 2015;Karki et al 2016;Wilson et al 2016;Lee et al 2017;Musarika et al 2017;Swenson et al 2019;Renou-Wilson et al 2019;Holl, Pfeiffer, and Kutzbach 2020;Rodriguez, Gerber, and Daroub 2020). For example, the CO 2 emission level decreased by 31% in agricultural fens after raising the water level by 20 cm (Matysek et al 2019).…”
Section: Effects Of Water Level Alteration On Co 2 Emissionsmentioning
confidence: 99%
“…A few studies have examined the GHG fluxes from restored peatlands using periodic (non-continuous) chamber measurements (e.g. Strack and Zuback 2013, Renou-Wilson et al 2019, Swenson et al 2019 but the spatial and temporal extrapolation required to achieve an annual balance introduces errors (Bubier et al 1999), limiting its utility to investigate climate impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the hydrological and ecological mechanisms controlling peatland response to climate changes is critical to predict potential feedbacks on the global C cycle (Baird et al 2012; The second assessment report… 2014). Recent field studies indicated that the peatland C balance represents a net C sink in intact peatlands in Canada (Wu et al 2010;Munir et al 2014;Webster et al 2018), China (zhu et al 2015zhou et al 2009), Finland (Laine et al 2019;Minkkinen et al 2018), Ireland (Swenson et al 2019), Scotland (Helfter et al 2015), Germany (Günther et al 2017), France (Leroy et al 2017), Poland (Acosta et al 2017), New zealand (Campbell et al 2014), East (Runkle et al 2013;Fleischer et al 2016;Eckhardt et al 2018;Davydov et al 2018) and Western part of Russia Kurganova et al 2011;Molchanov 2015;Ivanov et al 2017).…”
Section: Introductionmentioning
confidence: 99%